PENGEMBANGAN KARAKTER RELIGIUS DAN SOSIAL SISWA MADRASAH MELALUI PEMBELAJARAN BERBASIS NILAI-NILAI ISLAM: SYSTEMATIC LITERATURE REVIEW - Azyan, Rangga; Munawaroh, Nenden (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of religious and social character among students in various Madrasah Aliyah in Indonesia through learning activities based on Islamic values. Using a Systematic Literature Review approach, the research follows several stages including theme formulation, literature searching, article selection, data analysis, interpretation, drafting, and dissemination. The review focuses on three main aspects: the impact of character development, challenges faced by teachers and institutions, and the implications of technology integration in Islamic education. The findings indicate that Islamic value–based learning significantly contributes to shaping students who are religious, cooperative, responsible, and socially aware. However, challenges remain, such as limited teacher training, inadequate infrastructure, and resistance to pedagogical innovation. With stronger policy support and continuous professional development, character education grounded in Islamic values can effectively prepare students to be religious, creative, and adaptive in the digital era. Collaboration between schools, communities, and the government is essential to achieve holistic character development.